Faktor Lingkungan Yang Berkaitan Dengan Kejadian Leptospirosis di Kabupaten Pati Jawa Tengah - Pertiwi, Siti Maisyaroh Bakti; Setiani, Onny; Nurjazuli, Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: Leptospirosis is zoonotic disease caused by Leptospira bacteria and transmitted to human through contact with animal urine or environment is contaminated with this bacteria. Since 2010 Leptospirosis have increased, in Pati Regency, Central Java. In 2014 from January until Febuary the number of cases increased significantly compared to the previous year as 30 cases with 6 death. The purpose of the research is to identify risk faktors of phisical and biological environment that influence the incidence of leptospirosis at Pati regency. Methods: This research was an explanatory research with observational method using case control approach in 30 cases and 30 controls taken with inclusion criteria. The data of cases and controls obtained from medical records Pati Health District Agency. Diagnosis of control was taken based on clinical diagnosis and examination of blood supply using rapid test the type of Leptotek Lateral Flow with negative results.Results: The results of analysis showed there was relationship between the stagnant water of the ditch pools ((OR = 5,8; CI 1,03 – 32,84) and bad sewer condition with leptospirosis (OR = ( 7,1; 95% CI 2,01 – 25,11) . Test of water sample had been done at 8 location ans soil at 6 location. No one of them showed positif contain Leptospira sp.Conclusion: Stagnant water of ditch pools and bad sewer condition are influence of incidence of leptospirosis in Pati regency. There is one positive serum of mice that contained the bacteria Leptospira serovar bataviae with bacteria leptospira serovar bataviae.leptospirosis patients tend to spread in flood prone areas.Keywords : Leptospirosis, environmental risk factors